A novel approach for quantitation of glucosylceramide in human dried blood spot using LC–MS/MS. (July 2015) - Ji, Allena Ji; Wang, Haixing; Ziso-Qejvanaj, Enida; Zheng, Kefei; Chung, Lee Lee; Foley, Timothy; Chuang, Wei-Lien; Richards, Susan; Sung, Crystal
Background: Glucosylceramide, an efficacy biomarker for Gaucher Type 1 disease, exhibits poor solubility in polar solvents and whole blood which makes it difficult to prepare a homogenous blood standard.Results: We developed a novel method using standard addition approach by spiking a small volume of analyte solution on the surface of prespotted dried blood spot. The whole spots were punched out for subsequent extraction and LC–MS/MS analysis. The assay performance met all validation acceptance criteria. Glucosylceramide concentrations in 50 paired plasma and dry blood spot samples obtained from Gaucher Type 1 patients were tested and the results demonstrated the feasibility of using the DBS method for clinical biomarker monitoring.Conclusion: The new approach greatly improves assay precision and accuracy.